Evaluating the Implementation of the Flexicurity Concept Based on the Example of Selected EU Countries - Gawrycka , Małgorzata; Nagucka , Emilia (Studia Oeconomica Posnaniensia, 2014)
Existing discrepancies between the objectives of enterprises and the position of workers in the labour market has led to the popularization and implementation in many countries of the flexicurity model, the aim of which is to combine flexible forms of employment with effective policies supporting the transformation of the labour market. The aim of this study is to examine and evaluate the implementation of the flexicurity model, based on the adopted group of composite indicators. The scope of the study includes a review of the literature on the concept of flexicurity as well as collecting source materials which will be used in the empirical part of the research relating to the evaluation of the implementation of the flexicurity model in selected EU countries. The study will enable an assessment of the labour markets of the EU 21 economies from the point of view of security and labour market flexibility. The study will use elements of descriptive statistics and taxonomic methods.